Nano zerovalent zinc catalyzed peroxymonosulfate based advanced oxidation technologies for treatment of chlorpyrifos in aqueous solution: A semi-pilot scale study. (10th February 2020) - Shah, Noor S.; Khan, Javed Ali; Sayed, Murtaza; Khan, Zia Ul Haq; Iqbal, Jibran; Imran, Muhammad; Murtaza, Behzad; Zakir, Ali; Polychronopoulou, Kyriaki
Abstract: Chlorpyrifos (CPY), an organophosphate pesticide is largely used throughout the world on different crops for the control of pests and causes severe health and environmental issues. In this study, highly efficient, crystalline, and nm-rang sized zerovalent zinc (nZVZn) catalyst was synthesized and used for removal of chlorpyrifos at semi-pilot scale. The nZVZn showed high activity and caused 55% removal of CPY at 90 min time under the conditions of [CPY]0 = 10 mg/L, [nZVZn]0 = 1.0 g/L, and flow rate of the reactor = 0.2 L/min. Using identical conditions of [CPY]0, [nZVZn]0 and flow rate, the use of peroxymonosulfate (PMS) promoted the performance of nZVZn and caused 99.5% removal of CPY at [PMS]0 = 40 mg/L. The electron spin resonance (ESR) spectroscopy studies revealed that nZVZn catalyzed PMS reactions yield hydroxyl and sulfate radicals that degraded CPY and removal of CPY was suppressed by applying radical scavengers. The nZVZn catalyzed PMS based removal of CPY was optimum at high [PMS]0, [nZVZn]0 and low pH of solution. The flow rate of the pilot plant reactor also influenced the degradation efficiency of CPY. High pH of solution, high [CPY]0 as well as use of alcohols, NOM, and some inorganic ions inhibited removal of CPY by nZVZn catalyzed PMS. The analysis of degradation products (DPs) of CPY were used to propose degradation pathways of CPY. The high TOC removal of CPY, low leaching of Zn 2+ from Zn 0 into aqueous solution, and toxicity reduction of CPY suggest the nZVZn catalyzed PMS process to be highly effective and environmental benign for treatment of CPY. Graphical abstract: Image 1 Highlights: Nano zerovalent zinc was used for removal of chlorpyrifos at semi-pilot scale. Removal of chlorpyrifos by zerovalent zinc was promoted by peroxymonosulfate. Hydroxyl and sulfate radical rate constants with chlorpyrifos were calculated. Proposed degradation pathways of chlorpyrifos were suggested. Toxicities of treated chlorpyrifos solutions and zinc ion leaching were evaluated.